Effectiveness of Clinical Nursing Supervision to Improve Nursing Performance for Safety Nurse Care: A Literature Review - Masrifah Masrifah; Purwaningsih Purwaningsih; Nuzul Qur’aniati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nurses require supervision as a crucial leadership skill when working within a nursing team. The entire health team, including nurses, must provide high-quality, safe, and comprehensive health services due to the rapid development of technology and information. This study aims to assess the effectiveness of clinical nursing supervision in enhancing nursing performance for safe nurse care. The method used was a literatur review of journal databases within the last eight years (2016-2024). Search terms were constructed in collaboration with an academic librarian and were based on a PICOS structured question. Keywords adjusted to Medical Subject Heading (Mesh) phrases, namely “Clinical Supervision OR Supervision AND Nursing AND Performance”. All keywords were used in each database. Articles or journals there were included in the inclusion criteria were limited by year and language used according to the inclusion criteria. Online databases searched included Science Direct, Pubmed, WoS, and SAGE.. Studies were included in the review if they reported clinical nursing supervision to improve nursing performance for safety nurse care with quasy experiment or Experiment design. . Study show that six studies according to the specified inclusion criteria. Analysis of the results of this study using the Joanna Briggs Institute (JBI) tool. The review results indicate that effective clinical nursing supervision can enhance safety, serve as an educational model in conjunction with supervision to enhance nurses' performance in patient care, and improve the utilisation of the nursing process. It can be concluded that clinical nursing supervision can enhance patient safety and improve nurses' performance in patient care.